2011
DOI: 10.1111/j.1365-3016.2011.01234.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood lead levels and associated sociodemographic factors among preschool children in the South Eastern region of China

Abstract: Summary Children are especially vulnerable to lead toxicity, and exposure to lead has been linked to poor school performance and delinquency in children and adolescents. Even low-level lead exposure (blood lead level [BLL] lower than 10 µg/dL) can cause intelligence deficit. In China, BLLs in children decreased slightly after the phase-out of lead in gasoline, but few studies have examined the socio-demographic factors associated with BLL above 10 µg/dL. In thus study, we sought to examine the hypothesis that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
43
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 42 publications
8
43
1
Order By: Relevance
“…In agreement with previous studies (Tong et al 1996;Liu et al 2012), toddlers' BLLs were significantly higher than infants in this sample. Exposure to lead while growing up might be enhanced because of increasing activity level, time on the floor and mouthing and/or pica (Faustman et al 2000).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies (Tong et al 1996;Liu et al 2012), toddlers' BLLs were significantly higher than infants in this sample. Exposure to lead while growing up might be enhanced because of increasing activity level, time on the floor and mouthing and/or pica (Faustman et al 2000).…”
Section: Discussionsupporting
confidence: 93%
“…To the opposite, in a study conducted in China, boys had higher levels attributed to behavioural differences (Liu et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with previous studies [3,20,22,23,26]. The trends might be the comprehensive effects of several risk factors for lead exposure.…”
Section: Elementssupporting
confidence: 93%
“…Previous studies showed that the BLLs of boys were significantly higher than that of girls [3,[20][21][22]. This is thought to be the results of more outdoors activities of boys that leading to more chances of lead exposure.…”
Section: Elementsmentioning
confidence: 91%
“…Another important potential exposure of lead is likely to be lead dust from parents' work clothing which can be later ingested or inhaled by children at home [9]. However, in the present study we did not find occupation or other parental attributes determining the BLL in children, as also reported by other investigators [10][11][12].…”
Section: Discussionsupporting
confidence: 56%